Crochet for babies - Matela, Bobbie; Needlecraft Shop. ([Berne, IN] : Needlecraft Shop, 2007)
A collection of patterns for crocheting clothes, hats, blankets, and toys for infants and toddlers
Keywords: Crocheting -- Patterns; Infants' clothing